Inactivation of the tight junction gene CLDN11 by aberrant hypermethylation modulates tubulins polymerization and promotes cell migration in nasopharyngeal carcinoma - Hsin-Pai Li (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background Aberrant hypermethylation of cellular genes is a common phenomenon to inactivate genes and promote tumorigenesis in nasopharyngeal carcinoma (NPC). Methods Methyl binding domain (MBD)-ChIP sequencing of NPC cells, microarray data of NPC biopsies and gene ontology analysis were conducted to identify a potential tumor suppressor gene CLDN11 that was both hypermethylated and downregulated in NPC. Bisulfite sequencing, qRT-PCR, immunohistochemistry staining of the NPC clinical samples and addition of methylation inhibitor, 5’azacytidine, in NPC cells were performed to verify the correlation between DNA hypermethylation and expression of CLDN11. Promoter reporter and EMSA assays were used to dissect the DNA region responsible for transcription activator binding and to confirm whether DNA methylation could affect activator’s binding, respectively. CLDN11 was transiently overexpressed in NPC cells followed by cell proliferation, migration, invasion assays to characterize its biological roles. Co-immunoprecipitation experiments and proteomic approach were carried out to identify novel interacting protein(s) and the binding domain of CLDN11. Anti-tumor activity of the CLDN11 was elucidated by in vitro functional assay. Results A tight junction gene, CLDN11, was identified as differentially hypermethylated gene in NPC. High methylation percentage of CLDN11 promoter in paired NPC clinical samples was correlated with low mRNA expression level. Immunohistochemistry staining of NPC paired samples tissue array demonstrated that CLDN11 protein expression was relatively low in NPC tumors. Transcription activator GATA1 bound to CLDN11 promoter region − 62 to − 53 and its DNA binding activity was inhibited by DNA methylation. Re-expression of CLDN11 reduced cell migration and invasion abilities in NPC cells. By co-immunoprecipitation and liquid chromatography-tandem mass spectrometry LC-MS/MS, tubulin alpha-1b (TUBA1B) and beta-3 (TUBB3), were identified as the novel CLDN11-interacting proteins. CLDN11 interacted with these two tubulins through its intracellular loop and C-terminus. Furthermore, these domains were required for CLDN11-mediated cell migration inhibition. Treatment with a tubulin polymerization inhibitor, nocodazole, blocked NPC cell migration. Conclusions CLDN11 is a hypermethylated and downregulated gene in NPC. Through interacting with microtubules TUBA1B and TUBB3, CLDN11 blocks the polymerization of tubulins and cell migration activity. Thus, CLDN11 functions as a potential tumor suppressor gene and silencing of CLDN11 by DNA hypermethylation promotes NPC progression.